Modifying Layered Structure of Alkali Titanates via Vibratory Milling Technique - Tosapol Maluangnont; Naratip Vittayakorn (Integrated ferroelectrics, 2021)
In this work, the layered structure of lepidocrocite-type alkali titanates was modified via the vibratory milling technique. The Cs2Ti6O13, Cs0.7Zn0.35Ti1.65O4 and K0.8Zn0.4Ti1.6O4 systems were prepared by calcining the mixed oxide/(hydrogen)carbonate at 800 °C for 20 h with a heating rate of 10 °C/min and a cooling rate of 20 °C/min. After that, these powders were re-milled by vibratory milling for various times in order to study the effect of post-synthetic mechanical milling to structural modification and interlayer spacing. The phase formation of all powders was determined by using X-ray diffractometer (XRD). Lattice parameters and interlayer spacing of all samples were calculated from XRD peaks. The results showed that the single-phase of lepidocrocite-type Cs2Ti6O13 and Cs0.7Zn0.35Ti1.65O4 was maintained after milling, and the interlayer distance increased by 0.5%. Meanwhile, a mixture of expanded- and original one was observed for K0.8Zn0.4Ti1.6O4, with the interlayer expansion up to 1.4%. When compared three systems together which had different interlayer ions and alkali-to-titanium ratio, it was found that the interlayer distances of the Cs2Ti6O13 (Cs/Ti = 0.33) and Cs0.7Zn0.35Ti1.65O4 (Cs/Ti = 0.42) systems were not different because the relatively large Cs ion placed itself at the interlayer position. For the K0.8Zn0.4Ti1.6O4 system (K/Ti = 0.50), the interlayer distance was much lower than those of the Cs2Ti6O13 and Cs0.7Zn0.35Ti1.65O4 because of the smaller K ion.
Keywords: Ferroelectric and Piezoelectric Materials; Advanced ceramic materials synthesis; Bone Tissue Engineering Materials